2011
DOI: 10.1016/j.febslet.2011.12.002
|View full text |Cite
|
Sign up to set email alerts
|

The yeast metacaspase is implicated in oxidative stress response in frataxin‐deficient cells

Abstract: Edited by Vladimir SkulachevKeywords: Frataxin Friedreich ataxia Metacaspase Oxidative stress Yca1 a b s t r a c t Friedreich ataxia is the most common recessive neurodegenerative disease and is caused by reduced expression of mitochondrial frataxin. Frataxin depletion causes impairment in iron-sulfur cluster and heme biosynthesis, disruption of iron homeostasis and hypersensitivity to oxidants. Currently no pharmacological treatment blocks disease progression, although antioxidant therapies proved to benefit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…These results led the authors to suggest that the increased spontaneous nuclear damage in Δ yfh1 cells was caused by H 2 O 2 generated in the mitochondria (14). In line with this hypothesis, Δ yfh1 cells are extremely sensitive to H 2 O 2 treatment (21). In addition, different studies in yeast, Drosophila and patient fibroblasts showed that H 2 O 2 levels increase in frataxin-deficient cells (2224).…”
Section: Introductionmentioning
confidence: 72%
“…These results led the authors to suggest that the increased spontaneous nuclear damage in Δ yfh1 cells was caused by H 2 O 2 generated in the mitochondria (14). In line with this hypothesis, Δ yfh1 cells are extremely sensitive to H 2 O 2 treatment (21). In addition, different studies in yeast, Drosophila and patient fibroblasts showed that H 2 O 2 levels increase in frataxin-deficient cells (2224).…”
Section: Introductionmentioning
confidence: 72%
“…This suggests thus that the endopeptidase activity of Mca1p may directly degrade or at least impair mitochondria. This is relevant to a previously unexplained observation that deleting YCA1 from a frataxin-deficient yfh1⌬ strain that exhibits severe mitochondrial dysfunctions, allows the restoration of cytochromes assembly (49). YCA1 deletion may lower the rate of mitochondria degradation and thereby allow the synthesis and maintenance of partly functional mitochondria.…”
Section: Discussionmentioning
confidence: 96%
“…A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT 20 Recent advances in various ‗omics' technologies enable quantitative monitoring of the abundance of various biological molecules in a high-throughput manner, and thus allow determination of their variations between different biological states. In this study the integration of proteomics and metabolomics, has proved a potent tool of investigation on AA-PCD mechanisms dependent or independent on YCA1 and it will prove pivotal for understanding how the individual components in the system interact and influence overall cell metabolism and ultimately its fate.…”
Section: Discussionmentioning
confidence: 99%